Organoleptic evaluation of pear varieties grown at different sites - Takácsné Hájos, M.; Nyéki, J.; Szabó, Z. (International Journal of Horticultural Science, 2010)
It was stated as a summary that a system of testing pear varieties on scale of 100 degrees, weighing 11 properties, gives a comprehensive information on qualities of pear varieties. The points of the form to be filled out, distinguishes the appreciation of accessory flavours and tastes from the main properties. Under the title of taste, sweet and acid taste are evaluated separately. The presently used system is a step forward as the composed characters do not influence the judgement of each other. In the representation of results, the 100 degree system was more efficacious than the usual 5-point system because there was no need of using fractions, and the graphic profile is more expressive, so the commodity is better visualised. The assembly of the jury was divided into two groups as below and above 35 year old persons. The two groups judged differently the acidity, sweetness and the thickness of the fruit peel. It was suggested that the choice of the produce should consider the differences in taste and give up the idea of being equally favourable for both groups. The samples of different growing sites revealed that the best quality is produced at Nagykanizsa, and this capacity would be able to supply the market also in the large super-markets and chain of department stores in Hungary.